2-Amino-5-(3,4-dimethoxybenzylidene)-1-methylimidazol-4(5H)-one N,N-dimethylformamide monosolvate - Tvedte, Laura M. (International Union of Crystallography, 2010)
The crystal structure of the title compound, C(13)H(15)N(3)O(3)·C(3)H(7)NO, was determined as part of a larger project focusing on creatinine derivatives as potential pharmaceuticals. The molecule is essentially planar, in part because of intramolecular hydrogen bonding. Inversion-related pairs of molecules result from intermolecular hydrogen bonding. The π systems of 2-amino-5-(3,4-dimethoxybenzylidene)-1-methylimidazol-4(5H)-one and an inversion-related molecule overlap slightly, indicating a small amount of π–π stacking. Bond lengths, angles and torsion angles are consistent with similar structures, except in the imidazolone ring near the doubly bonded C atom, where significant differences occur.